2020
DOI: 10.7554/elife.51890
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cortex shapes sound responses in the inferior colliculus

Abstract: The extensive feedback from the auditory cortex (AC) to the inferior colliculus (IC) supports critical aspects of auditory behavior but has not been extensively characterized. Previous studies demonstrated that activity in IC is altered by focal electrical stimulation and pharmacological inactivation of AC, but these methods lack the ability to selectively manipulate projection neurons. We measured the effects of selective optogenetic modulation of cortico-collicular feedback projections on IC sound responses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 81 publications
5
51
0
Order By: Relevance
“…Therefore, bulk silencing may produce a mixture of effects that are difficult to interpret. More modern approaches using viralmediated delivery of optogenetic probes may solve some of these problems by permitting cell-type specific (Blackwell et al, 2020), layer-specific activation or silencing, and will permit activation or silencing to occur at the level of terminals, diminishing the likelihood of indirect effects stemming from changes in cochlear function.…”
Section: Methodological Issues In Top-down Modulation In the Subcortical Auditory Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, bulk silencing may produce a mixture of effects that are difficult to interpret. More modern approaches using viralmediated delivery of optogenetic probes may solve some of these problems by permitting cell-type specific (Blackwell et al, 2020), layer-specific activation or silencing, and will permit activation or silencing to occur at the level of terminals, diminishing the likelihood of indirect effects stemming from changes in cochlear function.…”
Section: Methodological Issues In Top-down Modulation In the Subcortical Auditory Systemmentioning
confidence: 99%
“…The projections are tonotopic (Lim and Anderson, 2007;Markovitz et al, 2013;Barnstedt et al, 2015) and the inhibition is presumably at least disynaptic because the corticocollicular system is thought to be excitatory (Feliciano and Potashner, 1995), and the suppression occurs in the later phases of the response (Popeláˇr et al, 2015). Corticocollicular fibers are responsible for protean functions at the level of the inferior colliculus, including facilitating adaptive changes in inferior colliculus neurons (Zhang et al, 2005;Wu and Yan, 2007;Bajo et al, 2010;Robinson et al, 2016;Asokan et al, 2018), sharpening of frequency tuning (Blackwell et al, 2020) and elicitation of escape responses (Xiong et al, 2015).…”
Section: Evidence That Auditory Corticofugal Systems Engage In Predictive Codingmentioning
confidence: 99%
“…The anesthetized preparation was deemed appropriate for these experiments as contrast gain control in the auditory cortex (Rabinowitz et al 2011) and midbrain (Lohse et al 2020) has been found to be unaffected by anesthesia. Similarly, research into the role of PV interneuron activity is routinely investigated in both awake (e.g., Natan et al 2017) and anesthetized (e.g., Atallah et al 2012) preparations, and no difference between these conditions was reported in experiments in which the effects of optogenetic activation of PV interneurons on activity in auditory cortex was examined (Blackwell et al 2020). Finally, anesthesia was a constant factor across conditions and so should not have been a relevant variable for the between-condition changes observed here.…”
Section: Methodsmentioning
confidence: 99%
“…The projections are tonotopic (Lim and Anderson, 2007;Markovitz et al, 2013;Barnstedt et al, 2015) and the inhibition is presumably at least disynaptic because the corticocollicular system is thought to be excitatory (Feliciano and Potashner, 1995), and the suppression occurs in the later phases of the response (Popelář et al, 2015). Corticocollicular fibers have been found to be responsible for protean functions at the level of the inferior colliculus, including facilitating adaptive changes in inferior colliculus neurons (Zhang et al, 2005;Wu and Yan, 2007;Bajo et al, 2010;Robinson et al, 2016;Asokan et al, 2018), sharpening of frequency tuning (Blackwell et al, 2020) and elicitation of escape responses (Xiong et al, 2015).…”
Section: Evidence That Auditory Corticofugal Systems Engage In Predicmentioning
confidence: 99%